Do the Fish Scales Shape of Mugil curema Reflect the Genetic Structure Using Microsatellites Markers and the Mexican Marine Ecoregions Classification? - Pacheco-Almanzar, Eloísa; Loza-Estrada, Nadia; Ibáñez, Ana L. (Frontiers in Marine Science, 2020)
Mugil curema is a teleost fish of economic importance that shows wide phenotypic variability in the coasts of Mexico. Intraspecific morphological variability might replicate either genetic dissimilarity between groups or environmental conditions according to phenotypic plasticity. Fish scales shape were used to discriminate location variants, genetic structure obtained by microsatellite markers and ichthyological provinces of Mexico. The present study uses landmarks and geometric morphometric statistical approaches to address the specific question: if and how fish scale shape varies with genetic structure or with ichthyological provinces. This is assessed using seven landmarks by scale, the coordinates of which were subjected to a generalized Procrustes analysis, followed by a principal components analysis and quadratic discriminant analysis with cross-validation analysis on shape. Also, the significance of classifications was assessed by Mancova. The proportion of total shape variance explained by total length and by centroid size was 3.8% and 3.0%, respectively. Therefore, only shape (without size), was used for the analysis. Mancova was significant in all cases, with locations, genetic structure and ichthyological provinces. The cross-validated discriminant analysis by location correctly classified 42.2% while with the genetic structure prearrangement and ichthyological provinces the identification rates were 58.3 and 57.0%, respectively. It was surprising that, as the same as in the genetic structure (microsatellite analysis), San Antonio Bay, Texas formed a group with Sabancuy, Campeche, Celestun and Sisal, Yucatan (the Caribbean locations). Likewise, Huave Lagoon System, Oaxaca located in the Pacific coast is more similar to the Caribbean sites unlike the other locations from the Pacific area, which are similar results depicted with microsatellite analysis. On the other hand, using the ichthyological provinces arrangement, the findings indicate that the Mexican and the Panamanian provinces were very different as opposed to the two provinces from the Gulf of Mexico more similar in fish scale shape. The Mexican province shows more identification rate (80.4%) while the rest of provinces discriminate less than 53.3%. Possibly, hydrographic features as currents or upwellings circumscribe boundaries between provinces and this could produce inherent genetic structure.